Analysis of a Non-Line-of-Sight Indoor Wireless Optical Communication Channel Model - Xiong, Ke; Wang, Hao; Yu, Pengzhang (International Journal of Computer Science and Information Technology, 2024)
Wireless Optical Communication (WOC) technology is a wireless communication method that uses light as a carrier. Traditional WOC systems often leverage the direct line-of-sight characteristic for communication, which can lead to issues with alignment between the transmitter and receiver, as well as the arrangement of indoor light sources. The paper introduces a method that employs diffuse reflection of light off indoor walls and ceilings to cover the entire indoor space, with a signal-to-noise ratio (SNR) that ranges from a maximum of 22.6721 to a minimum of 8.5738. This method allows for the receiver and transmitter to be non-stationary, greatly improving the flexibility of the WOC system. The paper studies the channel modeling of the direct link and the first reflection link in indoor WOC systems, and conducts simulation analysis of received power, signal-to-noise ratio, and impulse response in indoor space using an LED array.